Moisture Stability of Sulfide Solid Electrolytes: Systematic Comparison and Mechanistic Insight - Yusuke MORINO; Daisuke ITO; Misae OTOYAMA; Hirotada GAMO; Minami KATO; Nobuhiko TAKEICHI; Hikaru SANO (Electrochemistry)
All-solid-state batteries with sulfide solid electrolytes are promising next-generation energy storage devices owing to their longer lifetimes compared with liquid-type lithium-ion batteries. However, their practical application is hindered by low moisture stability. Few studies have quantitatively compared their moisture stability and underlying mechanisms among electrolyte species. This study systematically evaluates the moisture stability of sulfide solid electrolytes by standardizing particle size and varying electrolyte species, moisture content (dew point), and atmospheric conditions. Sulfide solid electrolytes with different crystal structures, such as Li6PS5Cl, Li3PS4, and Li4SnS4, were exposed to Ar gas flows with dew points from −30 to 0 °C (H2O concentrations: 0.45–4.8 g m−3). H2S generation followed the order: Li6PS5Cl ≫ Li3PS4 > Li4SnS4. At 0 °C dew point, H2S gas release was ∼22.7 ml g−1 for Li6PS5Cl, ∼0.44 ml g−1 for Li3PS4, and ∼0.17 ml g−1 for Li4SnS4. Despite variations in H2S generation, lithium ionic conductivity retention was similar. X-ray photoelectron spectroscopy showed surface hydrolytic decomposition species were observed on Li6PS5Cl, whereas Li3PS4 and Li4SnS4 showed minimal changes. Thermogravimetric analysis revealed clearer hydration in Li3PS4 and Li4SnS4, causing lower ionic conductivity without H2S generation. Differences in conductivity reduction are attributed to sulfide unit structures.